Biomimetics: Antimicrobial Microwebs of DNA–Histone Inspired from Neutrophil Extracellular Traps (Adv. Mater. 14/2019). Issue 14 (2nd April 2019) - Song, Yang; Kadiyala, Usha; Weerappuli, Priyan; Valdez, Jordan J.; Yalavarthi, Srilakshmi; Louttit, Cameron; Knight, Jason S.; Moon, James J.; Weiss, David S.; VanEpps, J. Scott; Takayama, Shuichi
Abstract : Inspired by the macromolecular weapons used by a type of white blood cell to capture and kill bacteria, in article number 1807436, J. Scott VanEpps, Shuichi Takayama, and co‐workers engineer nanofibrillar microwebs composed of DNA and histones that mimic neutrophil extracellular traps (NETs). The microwebs can enhance the killing activity of a last‐resort antibiotic against Escherichia coli even when it harbors a resistance gene.